2002
DOI: 10.1021/jf0106998
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat-Induced Aggregation on the IgE Binding of Patatin (Sol t 1) Is Dominated by Other Potato Proteins

Abstract: The interaction of the major potato allergen patatin, Sol t 1, with IgE was investigated on a quantitative level as a function of heat treatment at different temperatures. On the basis of a number of publications, potato is considered to be a heat-labile allergen, but the molecular explanation for this behavior was not given. In this work, heat treatment of patatin in the absence and presence of other potato proteins mimicking the proteinaceous environment of the potato was studied. Using far-UV circular dichr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…This was previously reported for other allergens [25,26,32] and fits well with the clinical observations that allergic individuals usually tolerate cooked food better than raw food [25]. We also found that heat-denatured allergens showed a lower potential to sensitise mice.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This was previously reported for other allergens [25,26,32] and fits well with the clinical observations that allergic individuals usually tolerate cooked food better than raw food [25]. We also found that heat-denatured allergens showed a lower potential to sensitise mice.…”
Section: Discussionsupporting
confidence: 92%
“…Heat-denaturation is well known to reduce the reactogenicity of allergens with IgE, as cooked foods are usually well or better tolerated by allergic individuals [24][25][26]. In this study, we tested whether this very simple strategy to reduce the reactogenicity of allergens might be useful for SIT, by investigating the effect of heat-denaturation on reactogenicity versus immunogenicity of several frequently used allergens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The allergen polymerization into high molecular weight molecules was previously observed with heat-treated Der f 2, 27 ovalbumin, 26,28 Sol t 1, 24 and Ara h 1. 29 By attenuated total reflectanceeFourier transform infrared spectroscopy, we demonstrated that thermally induced ProDer p 1 aggregation is associated with transformation of a-helical into b-sheet structures (data not shown).…”
Section: Discussionmentioning
confidence: 64%
“…However, some allergens may be thermostable like the major peanut allergen Ara h 1, such that the IgE-reactive conformational epitopes are resistant to heat-induced denaturation, as shown by Koppleman and coworkers [9] for roasting peanuts. In some cases, heat-treatment causes protein denaturation, followed by spontaneous renaturation during cooling, as reported for the potato allergen patatin 8Sol t 1) [10], which also appear to form aggregates with other potato proteins during thermal processing. Food proteins also undergo chemical interactions with other food components, such as amino acids with sugars.…”
Section: Food Processing -Change Of Proteomementioning
confidence: 71%